THE IMPACT OF HIGH BUSINESS RENTAL PRICES ON PRODUCT SELLING PRICES - Bekti Utomo; Dwi Dersmi Selan; Andriya Risdwiyanto (Adisam Publisher, 2025)
This literature research focuses on the impact of high business premises rental prices on product selling prices, a critical issue that influences business dynamics and consumer behavior. With rental costs rising, many businesses face the dilemma of maintaining profit margins without offloading additional costs to consumers. This research uses a literature review method to explore how rising rental prices affect pricing decisions by businesses, as well as consumer responses to these price changes. This research reveals that rising rental prices often force businesses to adjust selling prices, which can influence consumer purchasing behavior. Furthermore, this study highlights business strategies in managing high rental costs, including operational optimization and adoption of e-commerce business models to reduce dependence on physical locations. The research also discusses the long- term implications of rising rental prices on business sustainability and customer loyalty, and offers recommendations to stakeholders on how to navigate this challenge effectively. It is hoped that the results of this research can help businesses formulate responsive and innovative pricing strategies, as well as increase understanding of the dynamics of rental prices and their impact on the business ecosystem as a whole.